The eighth industrial fluid properties simulation challenge. - Schultz, Nathan E.; Ahmad, Riaz; Brennan, John K.; Frankel, Kevin A.; Moore, Jonathan D.; Moore, Joshua D.; Mountain, Raymond D.; Ross, Richard B.; Thommes, Matthias; Shen, Vincent K.; Siderius, Daniel W.; Smith, Kenneth D. (Adsorption Science & Technology, 2016)
The goal of the eighth industrial fluid properties simulation challenge was to test the ability of mol. simulation methods to predict the adsorption of org. adsorbates in activated carbon materials. In particular, the eighth challenge focused on the adsorption of perfluorohexane in the activated carbon BAM-109. Entrants were challenged to predict the adsorption in the the carbon at 273 K and relative pressures of 0.1, 0.3, and 0.6. Overall good agreement and consistency were found between the predictions of most entrants. [on SciFinder(R)]
Keywords: industrial fluid mol simulation property